2016
DOI: 10.1038/nature18956
|View full text |Cite
|
Sign up to set email alerts
|

A nucleosynthetic origin for the Earth’s anomalous 142Nd composition

Abstract: A long-standing paradigm assumes that the chemical and isotopic composition of many elements in the bulk silicate Earth are the same as in chondrites1–4. However, the accessible Earth has a greater 142Nd/144Nd than chondrites. Because 142Nd is the decay product of now-extinct 146Sm (t1/2= 103 million years5), this 142Nd difference seems to require a higher-than-chondritic Sm/Nd of the accessible Earth. This must have been acquired during global silicate differentiation within the first 30 million years of Sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 41 publications
5
107
0
Order By: Relevance
“…Traditionally, a uniform chondritic composition [chondritic uniform reservoir (CHUR)] of refractory trace elements has been assumed for the Earth-Moon system, but this was called into question by the finding of 142 Nd discrepancies between Earth and chondrites ( 17 ), suggesting that Earth (and, by extension, the Moon) might have formed with a nonchondritic Sm-Nd. However, Burkhardt et al ( 18 ) showed that this anomaly is actually the result of a small nucleosynthetic effect in Nd isotopic composition, which removes the only evidence for the Earth-Moon system deviating significantly from chondritic abundances of refractory trace elements. In addition, any nucleosynthetic effects (for example, in Hf isotopes) are thought to be small enough that they could not significantly affect Lu/Hf model ages ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, a uniform chondritic composition [chondritic uniform reservoir (CHUR)] of refractory trace elements has been assumed for the Earth-Moon system, but this was called into question by the finding of 142 Nd discrepancies between Earth and chondrites ( 17 ), suggesting that Earth (and, by extension, the Moon) might have formed with a nonchondritic Sm-Nd. However, Burkhardt et al ( 18 ) showed that this anomaly is actually the result of a small nucleosynthetic effect in Nd isotopic composition, which removes the only evidence for the Earth-Moon system deviating significantly from chondritic abundances of refractory trace elements. In addition, any nucleosynthetic effects (for example, in Hf isotopes) are thought to be small enough that they could not significantly affect Lu/Hf model ages ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…I am not likely to be around for the next major advances, one of which I think is going to involve using technological advances in geochemistry and astronomy to understand how planetary systems form. There has already been important progress (Burkhardt et al 2016, Bouvier & Boyer 2016. The arguments in these two papers clearly illustrate the importance not just of understanding the geochemical arguments involved, but also of thinking like a geochemist!…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that not all solar system materials are derived from the same proportions of nucleosynthetic sources (e.g., Burkhardt et al. ). This challenges the premise that the isotopic compositions of primitive meteorites are a perfect proxy for the composition of bulk planets.…”
Section: Objective 3: Quantitatively Determine the Evolutionary Timelmentioning
confidence: 99%